Réponses

2014-09-13T13:39:07+02:00
-3 * (-2,6 - 0,4 ) = -3 * (-3) = 9

 \frac{(-6) - (-1,5)}{1,8 + (-0,9)}
 \frac{-6+1,5}{0,8}  =  \frac{-4,5}{0,8}
tu peux le mettre sous cette forme aussi
- \frac{45}{8} = -5
1,8 - 0,9 = 0,9 et non pas 1,1, à corriger.
nouvelle édition !
J'ai vu :)
merci
Meilleure réponse !
  • Utilisateur Brainly
2014-09-13T13:44:53+02:00
A) - 3 x [(- 2,6) - (+ 0,4)]
  = - 3 x (- 2,6 - 0,4)
  = - 3 x (- 3)
  = 9

B) [(- 6) - (- 1,5)] : [1,8 + (- 0,9)]
  = (- 6 + 1,5) : (1,8 - 0,9)
  = - 4,5 : 0,9
  = - 5